Development of a low-cost microcontroller-based carbon capture device using the direct air capture (DAC) method and sodium hydroxide absorbent - Hamdani, Chalidia Nurin; Muhajir, Muhammad Hafiz; Akhiriyanto, Novan; Muhtadi, M. Zaky Zaim; Rosalinda, Hanny Megawati (Politeknik Negeri Lhokseumawe, 2025)
Currently, Carbon Capture, Utilization, and Storage (CCUS) systems are emerging as a significant focus in discussions of climate change. CCUS refers to a set of technologies designed to capture Carbon Dioxide (CO2) emissions from various sources and either utilize it for beneficial purposes or store it to prevent release into the atmosphere. CO2, the primary gas responsible for the greenhouse effect, is generated across multiple sectors, notably in energy and transportation. In Indonesia, the energy sector is the most significant contributor to CO2 emissions, accounting for 697.97 million tons in 2022. In this study, we have developed a cost-effective carbon capture device utilizing the Direct Air Capture (DAC) method. This device uses a microcontroller as the primary control unit, along with a compact closed chamber serving as the main reactor. Sodium hydroxide (NaOH) was utilized as the absorbent in our study. We conducted experiments on this device, keeping the NaOH concentration and reaction time fixed while varying the absorbent flow rate as the independent variable. The experiment yielded quite promising results. The absorption of CO2 is directly related to both the flow rate of the absorbent and the reaction time. The maximum CO2 absorption recorded is 3.960 ppm, achieved at a flow rate of 10 liters per minute with a reaction time of 5 minutes. The results have been reconfirmed by chemical titration.